Ursodeoxycholyl lysophosphatidylethanolamide modifies aberrant lipid profiles in NAFLD - Pathil-Warth, Anita; Liebisch, Gerhard; Okun, Jürgen G.; Chamulitrat, Walee; Schmitz, Gerd; Stremmel, Wolfgang (European journal of clinical investigation, 2015)
Background Hepatic fat accumulation with disturbed lipid homoeostasis is a hallmark of nonalcoholic fatty liver disease (NAFLD). The bile acid phospholipid conjugate Ursodeoxycholyl lysophosphatidylethanolamide (UDCA-LPE) is a novel anti-inflammatory agent with hepatoprotective effects in murine high-fat-diet (HFD)-induced NAFLD. The aim of this work was to study changes in the hepatic lipidome due to UDCA-LPE. Materials and methods High fat diet mouse model, mass spectometry, RT-PCR. Results Hepatic lipid extracts of HFD mice were analysed by mass spectrometry. The results determined higher levels of total, saturated, mono- and diunsaturated fatty acids (FA) in HFD mice, which were decreased by UDCA-LPE predominantly by the reducing the most abundant FA species palmitic acid and oleic acid. Unlike other FA species, levels of long-chain polyunsaturated fatty acids (LCPUFA), which are composed of arachidonic acid (ARA), eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), were increased in HFD mice upon UDCA-LPE treatment, mainly due to elevated hepatic ARA pools. Analysis of hepatic phospholipids species showed a decrease in total phosphatidylcholine (PC), especially monounsaturated PC (PUFA-PC) levels in HFD mice. Loss of total PC was reversed due to UDCA-LPE by increasing hepatic PUFA-PC pools. Gene expression analysis showed that UDCA-LPE upregulated PPARα, a key transcriptional regulator of fatty acid oxidation, as well as downstream target genes CPT1α and AOX, which are crucially involved in mitochondrial and peroxisomal fatty acid oxidation. Conclusion UDCA-LPE modulates defective fatty acid metabolism during experimental NAFLD thereby restoring altered lipid profiles in addition to its pronounced anti-inflammatory effects. Thus, UDCA-LPE may be a promising drug candidate for the management of NAFLD.
Gesehen am 01.07.2020